(untitled) (International journal of medical sciences, 2026)
In the era of globalization, which is becoming increasingly widespread, education abroad has become significant aspect of higher education, offering students to gain not only academic knowledge, but also valuable personal and professional experience. In this article, we will see how much studying abroad affects on their personal and professional development, and see research as an example, and their challenges as well.